Laparoscopic inguinal hernia repair in elderly patients: single center experience in 12 years - He, Zirui; Hao, Xiaohui; Li, Jianwen; Zhang, Yun; Feng, Bo; Yue, Fei; Xue, Pei; Gong, Hangjun (Annals of Laparoscopic and Endoscopic Surgery, 2017)
Background: To evaluate the clinical outcome of laparoscopic inguinal hernia repair (LIHR) in elderly patients. Methods: The clinical data of 3,203 cases (3,847 hernias) un-derwent LIHR from January 2001 to December 2013 were analyzed retrospectively. There were 1,677 transabdominal preperitoneal (TAPPs) in 1,475 cases, 2,154 total extraperito-neal (TEPs) in 1,718 cases and 16 intra-peritoneal onlay mesh (IPOMs) in 10 cases. All procedures were performed by the same surgical team and the choice of techniques was made by the surgeons. The follow-up period ranged from 23 to 60 months (median 43 months). Results: The hernias in elderly patients aged over 60 years ac-counted for 69.4%. These patients had more bilateral hernia, direct hernia and complex hernia than patients younger than 60 years (P=0.000, 0.000), more grade III hernia and grade IV hernia (P=0.000). There were more TEP and IPOM procedures in elderly patients (P=0.000), of which IPOMs were all used in recurrent hernias. There were more heavy-weight meshes used in elderly patients (P=0.000). No significant differences were found in operation time, visual analogue scales (VAS), postoperative hospital stay, cases returned to normal activities in 2 and 4 weeks between the two groups (P>0.05). There were no significant differences in recurrence rate and overall complication rate between the two arms (P>0.05), of which, there were more urinary retention in elder cases (P=0.008). No significant differences were found in seroma, transient paresthesia and ileus between two groups (P>0.05). Conclusions: LIHR is a safe and efficient technique in elderly patients. With reasonable application, LIHR can achieve good clinical outcome.